Pelayanan Kesehatan Komprehensif Untuk Lansia melalui Kolaborasi Dokter Multidisiplin di Desa Pandak - Arie Nugroho; Taufik Nur Yahya; Heryu Prima; Afifah Az Zahra; Viviane Annisa; Muhammad Zaed Fatahillah (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
The community service program conducted by a multidisciplinary team from the Faculty of Medicine, Universitas Islam Indonesia (FK UII) in Pandak Village, Bantul, successfully improved healthcare accessibility for the elderly through a proactive model. This model integrated metabolic screening, clinical examinations by specialists (surgeons, cardiovascular specialists, and orthopedic specialists), and preventive education. The activity took place at PAUD Melati, Pandak Hamlet, with 100 participants (reaching 100% of the target) ranging in age from 40 to 80 years. The community showed high enthusiasm and found this